The Effectiveness of Progressive Muscle Relaxation (PMR) Against Anxiety in Breast Cancer Patients Undergoing Chemotherapy at Dr Wahidin Sudirohusodo Hospital Makassar - Z, Ricky (Hasanuddin Medan, 2022)
Breast cancer is a malignant disease that most commonly attacks women. One pharmacological therapy for breast cancer is chemotherapy, but this treatment can cause anxiety due to the side effects it causes. Non-pharmacological treatment is really needed, one of which is Progressive Muscle Relaxation (PMR) which can reduce anxiety. The aim of the research was to determine the effectiveness of Progressive Muscle Relaxation (PMR) on anxiety in breast cancer patients. Sampling used purposive sampling technique. The total sample was 30 respondents (15 respondents were given PMR therapy) and (15 respondents were given deep breathing). Anxiety measurement uses the State Trait Anxiety Inventory (STAI) questionnaire. The test used to correlate PMR with disease duration is the Pearson test. Differences in cancer stage and mean anxiety score independent t-test. One-way anova test chemotherapy cycle. Meanwhile, the difference between pre and post PMR and control used the paired t-test. The results of the study showed no significant values for the duration of suffering from total anxiety p = 0.476, state anxiety p = 0.424, trait anxiety p = 0.464. At stage 3 it showed significant values for total anxiety p = 0.004, state anxiety p = 0.003, trait anxiety p = 0.018, at stage 4 total anxiety p = 0.009, state anxiety p = 0.009, trait anxiety p = 0.020. The chemotherapy cycle was not significant for total anxiety p = 0.084, and state anxiety p = 0.177, while trait anxiety showed a significant value of p = 0.026. Pre and post PMR showed significant values for total anxiety, state anxiety, and trait anxiety p = 0.001. The PMR and control groups showed significant values for PMR total anxiety, state anxiety, and trait anxiety p = 0.001 and the control was significant for total anxiety p = 0.028 and state anxiety p = 0.026, while trait anxiety was not significant p = 0.100. The mean anxiety scores (mean difference) of PMR and controls showed significant values for total anxiety p = 0.042, state anxiety p = 0.027 and trait anxiety p = 0.033. Conclusion Progressive Muscle Relaxation (PMR) exercise therapy is effective in reducing anxiety in breast cancer patients undergoing chemotherapy.